التسيير التقديري للموارد البشرية، الطرق النوعية والكمية للتنبؤ: مراجعة للادبيات - مدوكي يوسف (جامعة الوادي University of Eloued, 2024)
Human resource management plays a critical role in supporting the organization's strategic plan. All of its applications contribute positively to achieving the goal. Appreciative management of human resources is one of the most important practices of human resource management. Institutions rely on this approach to management to determine their current situation and future needs of the workforce. Thus, supporting other departments to get the best personnel. Therefore, there is a great need to get the best people in the right job at the right time. Forecasting helps match both the human resource needs and availability of the organization. There are two types of forecasting methods: qualitative and quantitative methods. The aim of this paper is to study the discretionary management of human resources by reviewing different theoretical literature. It also discusses the classification of forecasting techniques used and their various determinants.
Human Resources forecasting and planning, qualitative and quantitative forecasting methods: a Literature review
Keywords: التسيير التقديري; تقنيات التنبؤ الكمية; Human Resources